Healthy worker effect and changes in respiratory symptoms and lung function in hairdressing apprentices. Issue 11 (22nd October 2003) - Iwatsubo, Y; Matrat, M; Brochard, P; Ameille, J; Choudat, D; Conso, F; Coulondre, D; Garnier, R; Hubert, C; Lauzier, F; Romano, M C; Pairon, J C
Abstract : Aims: To compare the prevalence and incidence of respiratory symptoms and lung function values between hairdressing apprentices and office apprentices. Methods: A total of 322 hairdressing apprentices and 277 office apprentices (controls) were studied. Two cross sectional surveys were conducted in 1994 and 1996/97 with longitudinal follow up for a subgroup of apprentices (191 hairdressing apprentices and 189 office apprentices). Results: In the initial phase, the prevalence of respiratory symptoms was significantly lower among hairdressing apprentices than among office apprentices. Lung function test results showed significantly higher values for hairdressing apprentices. Non-specific bronchial reactivity was similar in the two groups. In the final phase, results for respiratory symptoms were similar. The incidence of respiratory symptoms was not significantly different between hairdressing apprentices and office apprentices. Subjects who dropped out had lower values for FVC and FEV1 in the initial phase than those who completed the final phase. There was a significant deterioration of FEV1 and FEF25–75% in hairdressing apprentices compared to office apprentices. There was a link between atopy and the incidence of most of the respiratory symptoms (day/night cough, wheezing, dyspnoea, mucosal hyperresponsiveness) and between smoking and the incidence of bronchial hyperreactivity. There was no significant correlation between change in lung function tests and specific hairdressing activities reported at the end of the apprenticeship or with environmental working conditions in hairdressing salons. Conclusions: Although a healthy worker effect can be suspected, results showed a significant deterioration of baseline values of lung function tests in the hairdressing apprentice group. However, no clear link was shown between change in lung function tests and specific parameters of occupational activities.